2022
DOI: 10.4238/gmr18980
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Resistance to orange rust associated with the G1 molecular marker in parents of Brazilian RB sugarcane varieties

Abstract: RB867515 (resistant to orange rust). Of the 63 sugarcane parents, 43 were classified as resistant, of which 27 were positive for the G1 marker; 10 as intermediate, including seven positives for G1; 10 were susceptible, among which four were positive for this marker. The molecular marker G1 showed an accuracy of 71% in predicting the resistant phenotype and could be used as a tool for the characterization of resistant germplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…On the other hand, Fier et al [ 32 ] observed high efficiency in predicting resistance using the G1 marker (71.43%) when evaluating 24 Brazilian commercial cultivars. Borella et al [ 73 ] evaluated 63 sugarcane progenitors preserved in the RIDESA germplasm bank and found that the molecular marker G1 was 71% accurate in predicting the resistance phenotype and thus could be used to characterize germplasm. There are different ways to classify resistant genotypes using a rating scale, and there is some evidence that more aggressive isolates or races of P .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Fier et al [ 32 ] observed high efficiency in predicting resistance using the G1 marker (71.43%) when evaluating 24 Brazilian commercial cultivars. Borella et al [ 73 ] evaluated 63 sugarcane progenitors preserved in the RIDESA germplasm bank and found that the molecular marker G1 was 71% accurate in predicting the resistance phenotype and thus could be used to characterize germplasm. There are different ways to classify resistant genotypes using a rating scale, and there is some evidence that more aggressive isolates or races of P .…”
Section: Discussionmentioning
confidence: 99%
“…Currently available diagnostic markers revealing sources of resistance to sugarcane diseases are useful for studying the frequency and distribution of resistance sources present in the germplasm, even in the absence of disease conditions in the field. They have been widely applied to identify parents carrying specific resistance sources [7][8][9][10][11]. Additionally, a well-planned production system requires not just one but several different resistance sources coexisting in the cultivated area to extend the useful life of such resistance genes.…”
Section: Molecular Markers In the Breeding Programmentioning
confidence: 99%